The Obamas [large type] - Kantor, Jodi, 1975- (Little, Brown and Company, 2012)
Kantor takes readers deep inside the White House as the Obamas try to grapple with their new roles, change the country, raise children, maintain friendships, and figure out what it means to be the first black President and First Lady.